Seed Coatings with Melatonin-Embedded Hydrogel Biopolymers as Green Tools to Mitigate Salinity Stress in Tomato Plants - Athanasiou, Kyriakos; Ioannou, Andreas; Georgiadou, Egli C.; Varaldo, Alice; Tarani, Evangelia; Chrissafis, Konstantinos; Fotopoulos, Vasileios; Krasia-Christoforou, Theodora (My University, 2025)
Improving plant tolerance against abiotic stress factors is important for sustaining global food security. Plants show prolonged, increased tolerance upon exposure to suboptimal environmental conditions when treated at the seed stage with certain chemical agents of natural or synthetic origin, resulting in higher crop yields. Polymers such as naturally derived hydrogels (HYDR) provide a smart delivery system for phytohormones. The protective effect of melatonin (Mel) and FOLICIST (Fol) applied directly or as calcium alginate-based hydrogel coatings with embedded Mel (HYDR-Mel) was studied in the "Dafni F1" tomato cultivar against salinity stress under in vitro conditions. An array of agronomic and biochemical parameters was evaluated, further to detailed material characterization, including germination-related parameters (such as the germination rate index, mean germination rate, speed of germination, and emergence index), morphological alternations (such as the main root length and root fresh weight), as well as cellular damage indicators (such as malondialdehyde (MDA) and H2O2 content). Findings suggest that engineered HYDR-Mel formulations are a promising "green" approach to mitigate abiotic stress effects in plants.
Keywords: abiotic stress; alginate; biostimulants; hydrogels; melatonin